2022
DOI: 10.21037/jgo-22-683
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic role of neutrophil-to-lymphocyte ratio and C-reactive protein in metastatic colorectal cancer using regorafenib: a systematic review and meta-analysis

Abstract: Background: The application of regorafenib has changed the landscape of subsequent-line treatment in metastatic colorectal cancer (mCRC). Baseline neutrophil-to-lymphocyte ratio (NLR) and C-reactive protein (CRP), as two of the most common inflammatory factors, are suggested to be potential prognostic factors for mCRC patients treated with regorafenib, but the results are conflicting. In this study, we conducted a metaanalysis to evaluate the prognostic role of NLR and CRP in mCRC patients treated with regoraf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…According to a meta-analysis including 16 studies by Zhou et al [ 45 ], higher CRP levels were associated with worse OS, cancer-specific survival, and PFS in prostate cancer. In a meta-analysis of 1287 subjects, Chen et al [ 46 ] reported that patients with metastatic colorectal cancer with higher CRP levels exhibited markedly reduced OS relative to those with lower CRP levels. Based on a meta-analysis including 4449 subjects, Chen et al [ 48 ] reported that higher CRP levels predicted dismal OS, cancer-specific survival, and PFS for head and neck squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…According to a meta-analysis including 16 studies by Zhou et al [ 45 ], higher CRP levels were associated with worse OS, cancer-specific survival, and PFS in prostate cancer. In a meta-analysis of 1287 subjects, Chen et al [ 46 ] reported that patients with metastatic colorectal cancer with higher CRP levels exhibited markedly reduced OS relative to those with lower CRP levels. Based on a meta-analysis including 4449 subjects, Chen et al [ 48 ] reported that higher CRP levels predicted dismal OS, cancer-specific survival, and PFS for head and neck squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, no publication bias, according to the authors, existed in the research shown in Figure 4. However, more than 10 articles used the funnel plot to assess publication bias (1). Furthermore, as sensitivity analysis is crucial for meta-analysis, we found that the author neglected to conduct it to strengthen the results.…”
mentioning
confidence: 96%
“…Secondly, the definitions of patients in the study of Zhao et (1). Thus, we recommend the authors choose the same criteria for a more precise and trustworthy result.…”
mentioning
confidence: 99%
See 2 more Smart Citations